Diseño e implementación de un prototipo inalámbrico que permita obtener las curvas características de paneles solares. - González Malla, Edgar Emanuel (2014)
This research project develops a methodology for obtaining the I-V and P-V curves of photovoltaic panels, through the "Design and Implementation of a Wireless Prototype, to obtain the Characteristic Curves of Panels and Solar Cells". The prototype enables characterize different technologies of cells and solar panels under some conditions of radiation and temperature, by sampling and varying the load resistance. This document is divided in the stages which are indicated below: In the literal d is specified the objectives to be achieved with the development of this project. In the literal e is indicated an introduction to the research project, indicating the factors that motivated implement it. In the literal f is presented a review of concepts and definitions necessary to understand the performance characteristics of the devices studied in this project, as well as the procedures followed in designing and implementing the same. The literal g contains the materials and methodologies used to meet the objectives proposed, comprising also the respective justifications for the procedures and the design considerations that were taken into account to obtain the best prototype. In the literal h are analyzed the results achieved with the design of the prototype through of the verifying of the correct operation using a photovoltaic panel 50 watts. In the literals i and j, is detailed the conclusions and recomendations respectively of the elaboration and operation of the prototype. Finally, in the literal l of annexes is added the cost of project development, the source code of the microcontrollers and a user manual about the operation del prototype.